Advancements in Microbial Pathogenesis and Molecular Diagnostics - Hamid, Mayssam Musab Rachid; Karim, Osama Ahmed Abdul; Mohammed, Sarab Riyadh Matnee; Humadi, Shaimaa Mahdi Abd Alghafor (American Journal of Biology and Natural Sciences, 2025)
Infectious diseases remain a major global health challenge, intensified by antimicrobial resistance, climate change, and the emergence of new pathogens. Despite significant advances in molecular biology, a knowledge gap persists regarding the early detection, host-pathogen interaction mechanisms, and effective control of infectious agents. This article provides an extensive review of recent progress in microbial pathogenesis and molecular diagnostics, including PCR, next-generation sequencing, microarray analysis, and bioinformatics tools. The analysis highlights how modern molecular techniques enhance pathogen identification, track antimicrobial resistance, and contribute to vaccine and therapeutic developments. Findings demonstrate that integrating molecular diagnostics into clinical practice significantly improves the accuracy and speed of diagnosing infectious diseases, leading to better patient outcomes and public health preparedness. However, challenges remain in data interpretation, regulatory approval, and ensuring access in low-resource settings. The study underscores the urgent need for interdisciplinary research and innovation to address these limitations and combat the evolving threat of infectious diseases.